(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Background: PDT is a targeted, minimally invasive cancer therapy limited by photosensitizer insolubility, instability, poor tumor selectivity, and shallow light penetration. Opportunity: Siddha Kayakarpam chromophores may act as natural photosensitizers but have low dispersibility and bioavailability. Nanoformulation: Encapsulate Kayakarpam-derived photosensitizers in liposomes or polymeric nanoparticles to improve solubility, stability, controlled release, and circulation. Targeting: Use EPR-mediated passive targeting and optional surface ligands for active tumor targeting to enhance tumor accumulation. Chronotherapy: Schedule dosing and light activation to exploit circadian tumor physiology, maximizing efficacy and minimizing normal-tissue damage. Deep activation: Incorporate nanoscintillators to convert X-rays to visible light, enabling activation in deep-seated tumors. Outcomes & evaluation: Expect increased ROS-mediated tumor kill, reduced systemic toxicity, and expanded PDT reach; evaluate via physicochemical characterization, in vitro ROS/phototoxicity assays, and in vivo biodistribution and efficacy studies.